Hollow spheres as nanocomposite fillers for aerospace and automotive composite materials applications. (1st December 2016) - Lapčík, Lubomír; Ruszala, Matthew J.A.; Vašina, Martin; Lapčíková, Barbora; Vlček, Jakub; Rowson, Neil A.; Grover, Liam M.; Greenwood, Richard W.
Abstract: There were studied four types of powder filler materials for polyolefin composite parts production for automotive and aerospace industry. There was confirmed, that the particle shape has a strong effect on the acoustic and mechanical properties of the powder bed as influenced by the varying packing density. The calcium carbonate spherical hollow particles exhibited the best aerodynamic performance when aerated and were completely fluidised. Simultaneously they were exhibiting the easy flowing behaviour as reflected in the observed flowability of 4.71. In contrary to this, the flat lamellar geometry of the precipitated calcium carbonate resulted in the worst fluidisation behaviour, as the aeration energy was 2.5× higher in comparison to the spherical particles. Remaining samples under study, i.e. flash calcined kaolin and dolomite powder, exhibited cohesive rheological behaviour as reflected in the observed flowability. There was found a clear correlation between powder rheological and electrostatic charge data with the observed acoustic performance as reflected in the frequency dependence of the normal incident sound damping coefficient. This was demonstrated by a relatively high increase in the damping efficiency with increasing porosity of the powder bed as reflected in the decreasing packing density. However the best fit was found between the absolute value of the electrostatic charge values and the sound damping properties. Graphical abstract: Highlights: Four types of powder filler materials for composite parts production were studied. Particle shape has a strong effect on the acoustic and mechanical properties of the powders. A clear correlation between electrostatic charge and acoustic performance was found. Hollow spheres demonstrated superior sound reflection properties.